Free Radical-Scavenging, Anti-Inflammatory, and Antibacterial Activities of Water and Ethanol Extracts Prepared from Compressional-Puffing Pretreated Mango (Mangifera indica L.) Peels - Chun-Yung Huang; Chia-Hung Kuo; Chien-Hui Wu; Ai-Wei Kuan; Hui-Ru Guo; Yu-Hua Lin; Po-Kai Wang (Journal of Food Quality)
During the processing of mango, a huge amount of peel is generated, which is environmentally problematic. In the present study, a compressional-puffing process was adopted to pretreat the peels of various mango cultivars, and then the bioactive compounds of mango peels were extracted by water or ethanol. The phenolic compound compositions as well as the free radical-scavenging, anti-inflammatory, and antibacterial activities of water extract (WE) and ethanol extract (EE) from nonpuffed (NP) and compressional-puffed (CP) mango peels were further evaluated. It was found that compressional-puffing could increase the yield of extracts obtained from most mango varieties and could augment the polyphenol content of extracts from Jinhwang and Tainoung number 1 (TN1) cultivars. The WE and EE from TN1 exhibited the highest polyphenol content and the greatest free radical-scavenging activities among the mango cultivars tested. Seven phenolic compounds (gallic acid, pyrogallol, chlorogenic acid, p-hydroxybenzoic acid, p-coumaric acid, ECG, and CG) were detected in CPWE (compressional-puffed water extract) and CPEE (compressional-puffed ethanol extract) from TN1, and antioxidant stability of both CPWE and CPEE was higher than that of vitamin C. Further biological experiments revealed that CPEE from TN1 possessed the strongest anti-inflammatory and antibacterial activities, and thus it is recommended as a multibioactive agent, which may have applications in the food, cosmetic, and nutraceutical industries.